Retroperitoneal cystic lymphangioma in a cirrhotic patient: a case report and review of the literature. : Retroperitoneal cystic lymphangioma in a cirrhotic patient. - Moreno Gonzales, Manuel Arturo (2023)
Retroperitoneal cystic lymphangiomas (RCL) are rare benign tumors of the lymphatic system. They account for less than 1% of all lymphangiomas and to date, less than 200 cases have been reported worldwide. Surgical resection is the recommended treatment option; however, obtaining a pre-operative diagnosis is often difficult and, in most cases, the final diagnosis is only possible following histological assessment of the surgical specimen. This report describes a case of RCL in a 58-year-old female cirrhotic patient who presented to our center with dull aching abdominal pain and distension. To our knowledge, this is the first case of a RCL in a cirrhotic patient reported in the literature.